Healthy and Unhealthy Plant-Based Diets and Body Weight in Breast Cancer Survivors: A Narrative Review - Angela D'Angelo; Sara Vitale; Elvira Palumbo; Livia SA Augustin (Epidemiology, Biostatistics and Public Health)
Obesity in breast cancer (BC) survivors increase the risk of BC recurrence, second primary BC, BC-specific mortality, and overall mortality. Guidelines for BC survivors encourage healthy lifestyles by promoting healthy diets, engage in physical activity and avoid weight gain to achieve longer survival and improved quality of life. In recent years, there has been a growing interest in the possible beneficial role of plant-based diets in body weight control and in BC risk and prognosis. Plant-based diets can be evaluated using dietary indices which provide a quantitative measure of how closely an individual’s diet aligns with a plant-based dietary pattern. However, there is a need to distinguish plant-based diets in healthy and unhealthy. This approach would address a research gap that often overlooks the quality and specific types of plant foods consumed. The aim of this narrative review is to analyze how a plant-based diet may impact on body weight in BC survivors, synthesizing existing evidence and discussing the potential mechanisms and implications. The findings suggest the importance of considering the quality of plant-based diets, as some may include vegetarian foods with a low nutritional profile which may negatively impact on body weight. This aspect could be crucial in preventing weight gain in women with BC, as body weight is considered a risk factor for poor BC prognosis and reduced survival.